Solid Soap Formulation with Ethanol Extract of Ginger Rhizome (Zingiber officinale Rosc.) Combination of Virgin Coconut Oil (Vco) and Palm Oil - Risma Andriani; Yani Ambari; Iif Hanifa Nurrosyidah (Universitas Airlangga, 2021)
Soap is a type of cleaning product that is used to clean dust, oil, dirt, germs, and bacteria that stick to the skin. Ginger is a plant that contains a wide range of antibacterial compounds including E. Coli, Staphylococcus aureus, B. Cereus, L monocytogenes and Candida albicans bacteria. Soap is made by chemically reacting sodium or potassium compounds with fatty acids derived from vegetable oil or animal oil. This study aims to determine the physical characteristics of solid soap with ginger rhizome extract with a combination of coconut oil and palm oil and analyze the panelist’s response to the soap produced. In the third week of observation, it is known that the water content ranges from 0,07%-0,1% with foam stability 71,11%-88,23% and pH 8,96-9,08. The most preferred solid soap based on the response of the panelist is soap from a mixture of coconut oil and palm oil with a ratio of 15:5.